Perfluorophenyl azide immobilization chemistry for single molecule force spectroscopy of the concanavalin A/mannose interaction - Madwar, Carolin (Langmuir : the ACS journal of surfaces and colloids, 2010)
The versatility of perfluorophenyl azide (PFPA) derivatives makes them useful for attaching a wide variety of biomolecules and polymers to surfaces. Herein, a single molecule force spectroscopy (SMFS) study of the concanavalin A/mannose interaction was carried out using PFPA immobilization chemistry. SMFS of the concanavalin A/mannose interaction yielded an average unbinding force of 70-80 pN for loading rates between 8000 and 40,000 pN/s for mannose surfaces on aminated glass, and an unbinding force of 57 ± 20 pN at 6960 pN/s for mannose surfaces on gold-coated glass. Dynamic force spectroscopy was used to determine the dissociation rate constant, k(off), for this interaction to be 0.16 s(-1)